Coating for improving oxidation resistance of chromium-nickel coating and preparation method thereof

By adding CEO2 and FEV80 modifiers to chromium nickel coatings, and performing high -temperature heat treatment in an inert atmosphere, the problem of poor oxidation film stability in the high -temperature steam environment is solved, which significantly improves the antioxidant performance and binding strength.

CN119372588APending Publication Date: 2025-01-28HUANENG HUNAN YUEYANG POWER GENERATION CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411286807.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing chromium-rich nickel coating has poor stability in high-temperature steam environments, resulting in rapid peeling of the oxide film and loss of protection against the matrix. The Cr content in the alloy matrix is ​​low, affecting the antioxidant properties.

Method used

By adding a modified agent CEO2 and FEV80 to the coatings, the critical concentration of the CR2O3 oxide film is reduced, the formation of mesh -like chromium carbide, and enhanced the density of the oxide film. Phenomenon, increase the intensity of the infiltration and coating with the mother material.

Benefits of technology

It significantly improves the antioxidant performance of chromium nickel coating in high -temperature steam environments, extended the service life of the coating, enhances the intensity of the binding of the coating and the mother material, and ensures effective protection of the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043316890000051
    Figure BDA0005043316890000051
  • Figure BDA0005043316890000061
    Figure BDA0005043316890000061
  • Figure BDA0005043316890000091
    Figure BDA0005043316890000091
Patent Text Reader

Abstract

The invention discloses a coating for improving oxidation resistance of a chromium-nickel coating, which is characterized in that after the surface of a workpiece to be plated is cleaned and preheated, coating slurry is uniformly sprayed on the surface of the workpiece, the spraying pressure is 0.5-2 MPa, and the thickness of a coating layer is 0.1-5 mm; and finally, carrying out high-temperature heat treatment to obtain the chromium-nickel anti-oxidation coating. Wherein the solid phase component of the slurry comprises the following components in percentage by mass: 50 to 80 percent of Cr, 15 to 45 percent of Ni, 2 to 6 percent of CeO2, 2 to 6 percent of FeV80 and 1 to 5 percent of NH4Cl. According to the method for improving the oxidation resistance of the chromium-nickel coating, the prepared infiltrated layer is uniform in organizational structure, moderate in thickness, sufficient in Cr atom diffusion, good in metallurgical bonding with a base body, not prone to falling off and suitable for austenitic steel and high-temperature alloy parts used for workpieces with the large length-diameter ratio and various complex shapes such as large boilers and oil and gas field conveying pipelines; and the method has excellent industrial batch production benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface alloying and coating preparation, and in particular relates to a coating for improving the oxidation resistance of a chromium-nickel coating. Background Art

[0002] In the power industry, pipe blockage and pipe burst accidents caused by scale problems on the inner walls of flow-through components account for more than 50% of boiler non-shutdown accidents, resulting in an increase of more than 20% in the operating and material costs of the unit; therefore, it is of great practical significance to research and develop anti-oxidation and corrosion-resistant technologies suitable for the inner and outer wall surfaces of pipes used in boiler units.

[0003] Studies have shown that high-temperature coatings are effective in solving problems such as oxidation corrosion, wear, and high-temperature ablation of components. However, taking chromium-nickel-rich coatings as an example, their anti-corrosion mechanism is different from that of aluminum-rich coatings. The service life is improved by increasing the anti-corrosion ability of the coating itself, but improvements are still needed to continue to improve the service life of the coating.

[0004] Studies have shown that high-temperature coatings have obvious effects in solving the problems of component oxidation corrosion, wear, and high-temperature ablation. However, taking chromium-rich nickel coatings as an example, their anti-corrosion mechanism is different from that of aluminum-rich coatings. By forming a dense Cr2O3 oxide film, the anti-corrosion ability of the coating itself is increased, thereby improving the service life. However, in order to continue to improve the service life of the coating, improvements are still needed. ZrO2, as a modifier, is widely used in the field of coatings, especially in chromium-rich coatings. The addition of ZrO2 can slow down the oxidation rate of chromium, thereby improving the anti-oxidation performance of the coating and extending the service life of the coating. However, Cr2O3 has poor stability in steam above 600°C, and the loose oxide film caused by volatile products causes the oxide film to peel off rapidly, thereby losing its protective effect on the substrate. In addition, the Cr content in the alloy matrix is ​​relatively low. As the service time increases, when the Cr content required for the growth of the oxide film is not supplemented, the anti-oxidation performance of the alloy will also drop sharply. Therefore, it is of great practical significance to study and develop new corrosion-resistant and anti-oxidation coatings suitable for the inner wall surface of pipelines for boiler units. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a coating that improves the oxidation resistance of the chromium-nickel coating.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a coating for improving the oxidation resistance of chromium-nickel coating, characterized in that: the coating comprises a solid phase component and a liquid phase component; the solid phase component comprises a permeation source Cr, Ni powder, an activator NH4Cl, a modifier CeO2 and FeV 80 The liquid phase components include solvent water glass, organic binder ethyl acetate and catalyst CrO3 solution.

[0009] As a preferred embodiment of the coating of the present invention, the solid phase components include 50-80% Cr, 15-45% Ni, 2-6% CeO2, 2-6% FeV 80 and 1-5% NH4Cl; wherein the Cr and Ni powders are sieved through a 1000-mesh sieve.

[0010] As a preferred embodiment of the coating of the present invention, the liquid phase components include, by volume fraction, 50-70% of water glass, 20-30% of ethyl acetate and 10-30% of CrO3 solution.

[0011] As a preferred embodiment of the coating of the present invention, the solid-to-liquid ratio of the solid phase component to the liquid phase component is 10g:4-6ml.

[0012] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a coating for improving the oxidation resistance of a chromium-nickel coating, comprising:

[0013] Weigh and prepare the solid phase component and the liquid phase component in proportion, and prepare the coating slurry after stirring and ball milling for use;

[0014] The workpiece to be plated is cleaned and preheated, and then the coating slurry is sprayed onto the workpiece surface, and dried and cured after coating;

[0015] The workpiece after the coating layer is solidified is placed in an inert atmosphere for high-temperature heat treatment, and after cooling, a chromium-nickel corrosion-resistant coating is obtained, and the coating residue is treated.

[0016] As a preferred embodiment of the preparation method of the present invention, the rotation speed of the ball mill is 350-400 rpm and the time is 6-24 hours.

[0017] As a preferred embodiment of the preparation method of the present invention, the preheating treatment is medium frequency preheating at 220°C for 30 to 60 minutes.

[0018] As a preferred embodiment of the preparation method of the present invention, the coating slurry is sprayed onto the surface of the workpiece, wherein the spraying pressure is 0.5-2MPa, the coating layer thickness is 0.1-5mm, and the coating coverage is not less than 98%.

[0019] As a preferred embodiment of the preparation method of the present invention, the drying is carried out by natural air drying for 24 to 48 hours, and the curing treatment is carried out by curing at 300 to 450° C. for 24 to 48 hours.

[0020] As a preferred embodiment of the preparation method of the present invention, the high temperature heat treatment temperature is 1000-1150°C, the holding time is 10-15 minutes, and the heat treatment atmosphere is an inert gas Ar or N2.

[0021] Beneficial effects of the present invention:

[0022] (1) The present invention adds modifiers CeO2, FeV 80 , reducing the critical concentration of Cr2O3 oxide film formation and reducing the formation of network chromium carbide, thus improving the antioxidant performance; further, the addition of rare earth oxides can pin the grain boundaries, refine the matrix structure, improve the surface hardness, and improve the bonding strength between the coating and the base material in the form of second phase precipitation on the basis of halide-promoted diffusion; in addition, rare earth oxides can reduce the critical concentration of C2O3 oxide film formation; in addition, the introduction of the modifier FeV 80 , which can inhibit the formation of network chromium carbide and improve the density of C2O3 oxide film.

[0023] (2) The present invention effectively avoids oxidation, hydrogen embrittlement and other phenomena that may occur in austenitic steel by heat treatment under an inert atmosphere, thereby protecting the workpiece matrix and increasing the penetration rate;

[0024] (3) The present invention prepares the coating through a slurry coating process, which is suitable for metal workpieces of various complex shapes and has strong universality;

[0025] (4) The present invention prepares the coating through an integrated production line, and the coating production efficiency is high, the thickness is controllable, the process repeatability is high, and it has strong practicality.

[0026] (5) The segmented slurry curing process of the present invention, which combines natural air drying with medium and low temperature curing, effectively avoids the problem of microcracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhances the bonding strength between the slurry layer and the workpiece surface; in addition, the use of rapid heating and short-term heat preservation to heat the workpiece prevents the rapid evaporation of slurry components at high temperatures. DETAILED DESCRIPTION

[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0030] The raw materials used in the present invention come from:

[0031] 99.95% Cr powder Sinopharm Chemical Reagent Co., Ltd. Specification: Alfa-013796

[0032] 99.8%Ni powder Sinopharm Chemical Reagent Co., Ltd. Specification: Alfa-000663

[0033] NH4ClSinopharm Chemical Reagent Co., Ltd. Specification: AR

[0034] 99.5%CeO2Sinopharm Chemical Reagent Co., Ltd. Specification: Alfa-044960

[0035] FeV 80 Hebei Luoqi New Material Technology Co., Ltd.

[0036] Sodium Silicate Sinopharm Chemical Reagent Co., Ltd. Specification: SigmaAldrich-338443-1L

[0037] Ethyl acetate Sinopharm Chemical Reagent Co., Ltd. Specification: AR

[0038] CrO3 solution Sinopharm Chemical Reagent Co., Ltd. Specification: AR.

[0039] Instruments used in the embodiments of the present invention: digital display constant temperature and constant speed magnetic stirrer Hangzhou Instrument and Motor Co., Ltd. 78HW-1 vertical planetary ball mill YXQM-2L desktop vacuum drying oven Jiangsu Xinchunlan Scientific Instrument Co., Ltd. DZF-6050 tubular furnace Tianjin Bona Thermoelectric Furnace Co., Ltd. BR-12NT-100 / 450.

[0040] Performance testing method in the embodiment of the present invention:

[0041] High-temperature steam oxidation test: The prepared chromium-nickel coating sample is placed in the constant temperature area of ​​the tube furnace. When the temperature in the tube furnace reaches the test temperature of 600°C, continuous water vapor is introduced into the reaction furnace through the steam generator at the front end, and the water vapor flow rate is constant at 0.34L / min. When the oxidation test is carried out for 200h, 300h, 500h and 800h, the sample is taken out, cleaned and dried, and the oxidized sample is weighed with an electronic balance.

[0042] Example 1

[0043] (1) Weigh the solid phase components according to mass ratio, including 50% Cr, 45% Ni, 2% CeO2, and 2% FeV 80 and 1% NH4Cl, and milled it in a planetary ball mill at 400 rpm for 24 h to obtain a solid phase penetration agent;

[0044] Subsequently, 60% of water glass, 20% of ethyl acetate and 20% of CrO3 solution were measured according to volume percentage, and the liquid phase components were obtained after being fully mixed, stirred, reacted and filtered for 8 hours;

[0045] Finally, the solid and liquid components were mixed at a solid-liquid ratio of 10 g:4 ml, and after being fully stirred for 4 hours, they were placed in a planetary ball mill at 400 rpm for 24 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.

[0046] (2) The workpiece surface was cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece was preheated at 220°C for 45 minutes by medium frequency, and the slurry was applied at a spray pressure of 2 MPa to a thickness of 3 mm at one time, maintaining a coating coverage of not less than 98%; then, the workpiece was naturally air-dried for 48 hours and cured at 450°C for 48 hours.

[0047] (3) The coated metal pipe is placed under Ar for heat treatment at a temperature of 1000°C and a holding time of 15 min. After completion, the residue on the surface of the workpiece is washed away with a high-pressure water gun or high-pressure air flow, and the workpiece is naturally air-dried.

[0048] The processes of Examples 2 to 11 are the same as those of Example 1. Examples 1 to 11 maintain the same ratio of solid phase components and liquid phase components. The specific conditions are detailed in Table 1. Table 1 is the specific parameters of Examples 1 to 11 of the method for improving the oxidation resistance of the chromium-nickel coating. According to the preparation steps in the above Example 1 and the specific preparation parameters in the table, chromium-nickel anti-oxidation coatings of different thicknesses and Cr atomic contents can be obtained.

[0049] Table 1 Preparation process parameters and diffusion layer parameters of chromium-nickel coatings in Examples 1 to 11

[0050]

[0051] By analyzing and studying the above embodiments, it is measured that the thickness of the diffusion layer is about 23-44 μm and the Cr atomic content is 22%-37%. The specific results are shown in Table 1.

[0052] The oxidation resistance of the chromium-nickel coatings prepared in Examples 1 to 11 in pure water vapor at 600° C. was tested. The test results are shown in Table 2.

[0053] Table 2 Mass changes of chromium-nickel coatings prepared in Examples 1 to 11 in 600°C pure water vapor (mg / cm 2 )

[0054]

[0055] It can be seen that the average oxidation rate of the chromium-nickel coatings prepared in Examples 1 to 11 in pure water vapor at 600°C is less than 0.1 mg / (cm 2 ·h), reaching the complete oxidation resistance level. Properly increasing the heat treatment temperature and extending the heat treatment time can increase the thickness of the prepared chromium-nickel coating and the Cr content in the coating, which is beneficial to improving the oxidation resistance of the coating in high-temperature steam.

[0056] Example 12

[0057] (1) Weigh the solid phase components according to mass ratio, including 80% Cr, 15% Ni, 2% CeO2, and 2% FeV 80 and 1% NH4Cl, and milled it in a planetary ball mill at 400 rpm for 24 h to obtain a solid phase penetration agent;

[0058] Subsequently, 70% of water glass, 20% of ethyl acetate and 10% of CrO3 solution were measured according to volume percentage, and the liquid phase components were obtained after being fully mixed, stirred, reacted and filtered for 8 hours;

[0059] Finally, the solid and liquid components were mixed at a solid-liquid ratio of 10 g:5 ml, and after being fully stirred for 4 hours, they were placed in a planetary ball mill at 400 rpm for 24 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.

[0060] (2) The workpiece surface was cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece was preheated at 220°C for 45 minutes by medium frequency, and the slurry was applied at a spray pressure of 2 MPa to a thickness of 3 mm at one time, maintaining a coating coverage of not less than 98%; then, the workpiece was naturally air-dried for 48 hours and cured at 450°C for 48 hours.

[0061] (3) The coated metal pipe is placed under Ar for heat treatment at a temperature of 1050°C and a holding time of 15 min. After completion, the residue on the surface of the workpiece is washed away with a high-pressure water gun or high-pressure air flow, and the workpiece is naturally air-dried.

[0062] Example 13

[0063] (1) Weigh the solid phase components according to mass ratio, including 60% Cr, 30% Ni, 6% CeO2, and 2% FeV 80 and 2% NH4Cl, which were placed in a planetary ball mill at 400 rpm for 24 h to obtain a solid phase penetration agent;

[0064] Subsequently, 55% of water glass, 20% of ethyl acetate and 25% of CrO3 solution were measured according to volume percentage, and the liquid phase components were obtained after sufficient mixing, stirring, reaction and filtering for 8 hours;

[0065] Finally, the solid and liquid components were mixed at a solid-liquid ratio of 10 g:5 ml, and after being fully stirred for 4 hours, they were placed in a planetary ball mill at 400 rpm for 24 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.

[0066] (2) The workpiece surface was cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece was preheated at 220°C for 45 minutes by medium frequency, and the slurry was applied at a spray pressure of 2 MPa to a thickness of 3 mm at one time, maintaining a coating coverage of not less than 98%; then, the workpiece was naturally air-dried for 48 hours and cured at 450°C for 48 hours.

[0067] (3) The coated metal pipe is placed under Ar for heat treatment at a temperature of 1050°C and a holding time of 15 min. After completion, the residue on the surface of the workpiece is washed away with a high-pressure water gun or high-pressure air flow, and the workpiece is naturally air-dried.

[0068] Embodiment 14

[0069] (1) Weigh the solid phase components according to mass ratio, including 50% Cr, 33% Ni, 6% CeO2, and 6% FeV 80 and 5% NH4Cl, and milled it in a planetary ball mill at 400 rpm for 24 h to obtain a solid phase penetration agent;

[0070] Subsequently, 50% of water glass, 20% of ethyl acetate and 30% of CrO3 solution were measured according to volume percentage, and the liquid phase components were obtained after sufficient mixing, stirring, reaction and filtering for 8 hours;

[0071] Finally, the solid and liquid components were mixed at a solid-liquid ratio of 10 g:5 ml, and after being fully stirred for 4 hours, they were placed in a planetary ball mill at 400 rpm for 24 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.

[0072] (2) The workpiece surface was cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece was preheated at 220°C for 45 minutes by medium frequency, and the slurry was applied at a spray pressure of 2 MPa to a thickness of 3 mm at one time, maintaining a coating coverage of not less than 98%; then, the workpiece was naturally air-dried for 48 hours and cured at 450°C for 48 hours.

[0073] (3) The coated metal pipe is placed under Ar for heat treatment at a temperature of 1050°C and a holding time of 15 min. After completion, the residue on the surface of the workpiece is washed away with a high-pressure water gun or high-pressure air flow, and the workpiece is naturally air-dried.

[0074] Embodiment 15

[0075] (1) Weigh the solid phase components according to mass ratio, including 65% Cr, 25% Ni, 4% CeO2, and 2% FeV 80 and 4% NH4Cl, which were placed in a planetary ball mill at 400 rpm for 24 h to obtain a solid phase penetration agent;

[0076] Subsequently, 55% of water glass, 30% of ethyl acetate and 15% of CrO3 solution were measured according to volume percentage, and the liquid phase components were obtained after sufficient mixing, stirring, reaction and filtering for 8 hours;

[0077] Finally, the solid and liquid components were mixed at a solid-liquid ratio of 10 g:5 ml, and after being fully stirred for 4 hours, they were placed in a planetary ball mill at 400 rpm for 24 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.

[0078] (2) The workpiece surface was cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece was preheated at 220°C for 45 minutes by medium frequency, and the slurry was applied at a spray pressure of 2 MPa to a thickness of 3 mm at one time, maintaining a coating coverage of not less than 98%; then, the workpiece was naturally air-dried for 48 hours and cured at 450°C for 48 hours.

[0079] (3) The coated metal pipe is placed under Ar for heat treatment at a temperature of 1150°C and a holding time of 10 min. After completion, the residue on the surface of the workpiece is washed away with a high-pressure water gun or high-pressure air flow, and the workpiece is naturally air-dried.

[0080] Example 16

[0081] (1) Weigh the solid phase components according to mass ratio, including 65% Cr, 20% Ni, 5% CeO2, and 5% FeV 80 and 5% NH4Cl, and milled it in a planetary ball mill at 400 rpm for 24 h to obtain a solid phase penetration agent;

[0082] Subsequently, 65% of water glass, 25% of ethyl acetate and 10% of CrO3 solution were measured according to volume percentage, and the liquid phase components were obtained after sufficient mixing, stirring, reaction and filtering for 8 hours;

[0083] Finally, the solid and liquid components were mixed at a solid-liquid ratio of 10 g:5 ml, and after being fully stirred for 4 hours, they were placed in a planetary ball mill at 400 rpm for 24 hours. After completion, a uniformly mixed slurry was obtained, which was the coating slurry.

[0084] (2) The workpiece surface was cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece was preheated at 220°C for 45 minutes by medium frequency, and the slurry was applied at a spray pressure of 2 MPa to a thickness of 3 mm at one time, maintaining a coating coverage of not less than 98%; then, the workpiece was naturally air-dried for 48 hours and cured at 450°C for 48 hours.

[0085] (3) The coated metal pipe is placed under Ar for heat treatment at a temperature of 1150°C and a holding time of 15 min. After completion, the residue on the surface of the workpiece is washed away with a high-pressure water gun or high-pressure air flow, and the workpiece is naturally air-dried.

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 13 is that the solid phase components in step (1) are replaced by: 60% Cr, 30% Ni, 8% CeO2 and 2% NH4Cl.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 13 is that the solid phase components in step (1) are replaced by: 60% Cr, 30% Ni, 8% FeV 80 and 2% NH4Cl.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 13 is that the solid phase components in step (1) are replaced by: 60% Cr, 30% Ni, 8% ZrO2 and 2% NH4Cl.

[0092] Comparative Example 4

[0093] The difference between this comparative example and Example 13 is that the ratio of the liquid phase components in step (1) is replaced by: 70% water glass and 30% ethyl acetate.

[0094] Comparative Example 5

[0095] The difference between this comparative example and Example 13 is that the liquid phase components in step (1) are replaced by: 55% water glass, 20% acrylic resin and 25% CrO3 solution.

[0096] Comparative Example 6

[0097] The difference between this comparative example and Example 13 is that the solid-liquid ratio in step (1) is replaced by 10:6.

[0098] The oxidation resistance of the chromium-nickel coatings prepared in Example 1, Examples 12 to 16 and Comparative Examples 1 to 6 in pure water vapor at 600° C. was tested. The test results are shown in Table 3.

[0099] Table 3 Mass changes of chromium-nickel coatings prepared in Examples 1, 12-16 and Comparative Examples 1-7 in 600°C pure water vapor (mg / cm 2 )

[0100]

[0101]

[0102] It can be seen that compared with adding only CeO2, FeV 80 Compared with the modification of coating by CeO2 and FeV 80 The combined effect can significantly reduce the formation of network chromium carbide in the coating, improve the density of the Cr2O3 oxide film generated at high temperature, improve the coating quality, reduce the oxidation rate of the prepared chromium-nickel coating in 600°C steam by more than 35%, and improve the coating's anti-oxidation performance at high temperatures.

[0103] In summary, the present invention provides a coating for improving the oxidation resistance of the chromium-nickel coating. Under the conditions of adjusting the main process parameters such as the content of solid phase penetrant component, the content of modifying elements, the solid-liquid ratio of the slurry, the slurry spraying pressure, the coating layer thickness and the heat treatment parameters, a chromium-nickel anti-oxidation coating with a good metallurgical bond and a thickness of 23-44 μm and a Cr atomic content of 22%-37% is prepared; the chromium-nickel coating obtained by the present invention has an oxidation resistance that is 17-62 times higher than that of the base material in a 600°C pure water vapor environment, and an oxidation resistance that is 19-74 times higher than that of the base material in a 650°C pure water vapor environment. This shows that the chromium-nickel coating prepared by the method of the present invention effectively improves the oxidation resistance of the alloy base material in a water vapor environment.

[0104] The method of improving the oxidation resistance of the chromium-nickel coating in the present invention is suitable for austenitic steel and high-temperature alloy parts used in large boilers, oil and gas field transportation pipelines and other workpieces with large aspect ratios and various complex shapes. It has strong practicality, high permeation rate, excellent membrane-base bonding, and extremely good industrial mass production benefits.

[0105] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A coating for improving the oxidation resistance of a chromium-nickel coating, characterized in that: The coating comprises a solid phase component and a liquid phase component; the solid phase component comprises a seepage source Cr, Ni powder, an activator NH4Cl, a modifier CeO2 and FeV 80 ; The liquid phase components include solvent water glass, organic binder ethyl acetate and catalyst CrO3 solution; The solid phase components include 50-80% Cr, 15-45% Ni, 2-6% CeO2, 2-6% FeV 80 And 1-5% NH4Cl.

2. The coating according to claim 1, characterized in that: The Cr and Ni powders were sieved through a 1000-mesh sieve.

3. The coating according to claim 1, characterized in that: The liquid phase components include 50-70% of water glass, 20-30% of ethyl acetate and 10-30% of CrO3 solution by volume.

4. The coating according to claim 1, characterized in that: The solid-to-liquid ratio of the solid phase component to the liquid phase component is 10g:4-6ml.

5. The method for preparing a coating for improving the oxidation resistance of a chromium-nickel coating according to any one of claims 1 to 4, characterized in that: include, Weigh and prepare the solid phase component and the liquid phase component in proportion, and prepare the coating slurry after stirring and ball milling for use; The workpiece to be plated is cleaned and preheated, and then the coating slurry is sprayed onto the workpiece surface, and dried and cured after coating; The workpiece after the coating layer is solidified is placed in an inert atmosphere for high-temperature heat treatment, and after cooling, a chromium-nickel corrosion-resistant coating is obtained, and the coating residue is treated.

6. The preparation method according to claim 5, characterized in that: The ball milling speed is 350-400 rpm and the time is 6-24 hours.

7. The preparation method according to claim 5, characterized in that: The preheating treatment is medium frequency preheating at 220° C. for 30 to 60 minutes.

8. The preparation method according to claim 5, characterized in that: The coating slurry is sprayed onto the surface of the workpiece, wherein the spraying pressure is 0.5-2MPa, the coating layer thickness is 0.1-5mm, and the coating coverage is not less than 98%.

9. The preparation method according to claim 5, characterized in that: The drying is carried out by natural air drying for 24 to 48 hours, and the curing treatment is carried out by curing at 300 to 450° C. for 24 to 48 hours.

10. The preparation method according to claim 5, characterized in that: The high temperature heat treatment temperature is 1000-1150° C., the heat preservation time is 10-15 minutes, and the heat treatment atmosphere is an inert gas Ar or N2.

Citation Information

Cited By

  • Modification method for improving corrosion resistance of chromium-nickel cladding coating

    CN120006280A